Melodic High Tones in Emihavani - Kisseberth, Charles; Mtenje, Al (Stellenbosch Papers in Linguistics Plus, 2022)
Emihavani is a Bantu language spoken in southeastern Malawi. It is a dialect of Emakhuwa, a language whose origins lie in Nampula Province in northern Mozambique, but whose speakers have migrated into both southern Tanzania and southeastern Malawi. It is important to note that all of the regions where Emakhuwa dialects are spoken are economically under-developed, and a consequence of this is that the language, despite being spoken by several million people, is one of the poorer documented major Bantu languages (cf. Guérois 2015, Katupha 1983, 1991, Kisseberth 2003, Kisseberth & Guérois 2014, Stucky 1985, Van der Wal 2009). The present paper starts to remedy this situation for Emihavani by providing an account of the most complicated aspect of the Emihavani tonal system: the “melodic High tone” patterns that operate in the verbal system. In order to document these tone patterns, we will necessarily have to provide a brief discussion of several aspects of Emihavani phonology and morphology. We should emphasize that all of the material in this paper derives from our intensive research on Emihavani that began in 2017. All of the data reflects the speech of Alfred Lihelu, a native speaker who has been part of all the significant research on Emihavani in the past few years (e.g. the translation and recording of the New Testament in 2014 by the Bible Society of Malawi). Although our focus is definitely on Emihavani, we also seek to place Emihavani in its proper Emakhuwa context. All references to other Emakhuwa dialects derive from the first-named author’s research over more than four decades.